Cognitive reserve and the severity of Alzheimer’s disease - Sobral, M. (2015)
Alzheimer's disease (AD) is a clinical syndrome caused by neurodegeneration and characterized by a progressive deterioration in cognitive ability and capacity for independent living. Cognitive reserve (CR) describes the capacity of the adult brain to cope with the effects of the neurodegenerative process and to minimize the clinical manifestation of pathology of dementia. The aim of this study was to evaluate the association of CR and the severity of AD. Method: This study was cross-sectional. Functional and neuropsychological abilities of 75 outpatients with probable AD diagnosis were evaluated. Patients completed two questionnaires, "Participation in leisure activities throughout life" and CR Questionnaire. Result: The relationship between Clinical Dementia Rating (CDR) and the level of CR was statistically significant (likelihood ratio (LR), p = 0.015). Conclusion: The level of CR influenced the severity of dementia. This study suggests that AD patients with higher CR may benefit against cognitive decline after diagnosis of AD.